Music and Dance in respiratory disease management in Uganda: A qualitative study of patient and healthcare professional perspectives - Philip, Keir E. J.; Cartwright, Lucy L.; Westlake, Debra; Nyakoojo, Grace; Kimuli, Ivan; Kirenga, Bruce; Brakema, Evelyn A.; Orme, Mark W.; Fancourt, Daisy; Hopkinson, Nicholas S.; Jones, Rupert; Katagira, Winceslaus (medRxiv, 2021)
Music and dance are increasingly used as adjunctive arts-in-health interventions in high-income settings, with a growing body of research suggesting biopsychosocial benefits. Such low-cost, low-resource interventions may have application in low-resource settings such as Uganda. However, research on perceptions of patients and healthcare professionals regarding such approaches is lacking. We delivered taster music and dance for chronic respiratory disease (CRD) sessions to patients and healthcare professionals. We then conducted an exploratory qualitative study, using thematic analysis of semi-structured interviews with the healthcare professionals and patients regarding i) the role of music and dance in Ugandan life and ii) the perceived acceptability and feasibility of using music and dance in CRD management in Uganda.
Keywords: Music; Dance; Respiratory disease management; Uganda; Patient; Healthcare